Jim Black interview - Black, Jim; Wolfleg, Allan J. (Canadian Plains Research Centre, 1974)
26 p. transcript of an interview with Jim Black, conducted by Allan J. Wolfleg on January 18, 1974. Tape number IH-AA.226, transcript disc 39. An interview discussing various topics: evidence given to the Office of Specific Claims and Research by Jim Black; signing of Treaty #7; an account of the CPR line being taken through Blackfoot Reserve territory; a description of two murders: Frank Skynner killed by Scrapings, and Charcoal's murder of Medicine Pipe Stem; the surrender of Blackfoot Reserve land; and an understanding of land rights. Other no